Penghayatan dan Pengalaman Pancasila dalam Refleksi Matius 22:37-40 - Desti Samarenna (JURNAL TERUNA BHAKTI, 2020)
The Law of Love is at the heart of the Christian faith mentioned by Jesus in Matthew 22: 37-40. Within the framework of national life, Christians also continue to carry out their responsibility to live and practice the values of Pancasila as the basis of national life. As Christians, the practice of Pancasila cannot be separated from implementing the Law of Love. This article is a literature review with a qualitative approach to the text of Matthew 22: 37-40 about love for God and love for humans. The purpose of writing is to apply the text of Matthew 22: 37-40 in the context of living Pancasila as a philosophy of living together within the framework of nationalism. The method that the author uses is a description of the text analysis of Matthew 22: 37-40, to provide an explanation and understanding of Matthew's view of faith and its relation to Pancasila, where the value of the One and Only Godhead is the basis of humanity that builds, maintains and develops Indonesian unity. In conclusion, loving God to become and others becomes the basis for being together as a form of living Pancasila. Abstrak Hukum Kasih merupakan inti dari iman Kristen yang disebutkan oleh Yesus dalam Matius 22:37-40. Dalam kerangka hidup berbangsa, maka orang Kristen pun tetap melakukan tanggung jawabnya untuk menghayati dan mengamalkan nilai-nilai Pancasila sebagai dasar hidup berbangsa. Sebagai orang Kristen, maka pengamalan Pancasila tidak lepas dari mengimplementasikan Hukum Kasih. Artikel ini merupakan kajian literatur dengan pendekatan kualitatif terhadap teks Matius 22:37-40 tentang kasih kepada Allah dan kasih terhadap manusia. Tujuan penulisan adalah menerapkan teks Matius 22:37-40 dalam konteks menghayati Pancasila sebagai falsafah hidup bersama dalam kerangka nasionalisme. Metode yang penulis lakukan adalah deskripsi analisis teks Matius 22:37-40, untuk memberikan penjelasan dan pemahaman pandangan Matius tentang iman dan kaitannya dengan Pancasila di mana nilai keTuhanan Yang Maha Esa menjadi basis kema-nusiaan yang membangun, memelihara dan mengembangkan persatuan Indonesia. Kesim-pulannya, mengasihi Allah menjadi dan sesama menjadi dasar untuk bersama sebagai bentuk penghayatan Pancasila.